Modification of polypropylene separator with multifunctional layers to achieve highly stable sodium metal anode - Chishti, Aadil Nabi; Iqbal, Sikandar; Ali, Muhammad; Ali, Moazzam; Aman, Samia; Hussain, Hamid; Yousaf, Muhammad; Jiang, Yinzhu (Journal of energy chemistry, 2025)
The modified PP separators with HCS layer ensure uniform sodium ion flux, while NaF layer reduces the sodium ion diffusion barrier, and their synergistic effects improve the electrochemical performances of SMBs. [Display omitted] Separator modification is an effective approach to suppress dendrite growth to realize high-energy sodium metal batteries (SMBs) in practical applications, however, its success is mainly subject to surface modification. Herein, a separator with multifunctional layers composed of N-doped mesoporous hollow carbon spheres (HCS) as the inner layer and sodium fluoride (NaF) as the outer layer on commercial polypropylene separator (PP) is proposed (PP@HCS-NaF) to achieve stable cycling in SMB. At the molecular level, the inner HCS layer with a high content of pyrrolic-N induces the uniform Na+ flux as a potential Na+ redistributor for homogenous deposition, whereas its hollow mesoporous structure offers nano-porous buffers and ion channels to regulate Na+ ion distribution and uniform deposition. The outer layer (NaF) constructs the NaF-enriched robust solid electrolyte interphase layer, significantly lowering the Na+ ions diffusion barrier. Benefiting from these merits, higher electrochemical performances are achieved with multifunctional double-layered PP@HCS-NaF separators compared with single-layered separators (i.e. PP@HCS or PP@NaF) in SMBs. The Na||Cu half-cell with PP@HCS-NaF offers stable cycling (280 cycles) with a high CE (99.6%), and Na||Na symmetric cells demonstrate extended lifespans for over 6000 h at 1 mA cm−2 with a progressively stable overpotential of 9 mV. Remarkably, in Na||NVP full-cells, the PP@HCS-NaF separator grants a stable capacity of ∼81 mA h g−1 after 3500 cycles at 1 C and an impressive rate capability performance (∼70 mA h g−1 at 15 C).